A new NASICON-type polyanion, LixNi2(MoO4)3 as 3-V class positive electrode material for rechargeable lithium batteries - BEGAM, K (2004)
This paper presents our success in synthesizing a new framework type LixNi2(MoO4)(3) (0 less than or equal to x less than or equal to 4) polyanion compound by adopting a novel aqueous soft-combustion process. The annealed powders exhibited a single-phase structure as confirmed by X-ray diffraction (XRD) and were characterized by electrochemical techniques in order to elucidate the suitability of this new material as positive electrode material in rechargeable lithium-containing batteries. The morphology of the heated product was found to be composed of soft agglomerates embedded by submicrometre spherical grains. The electrode-active character of the new material was examined in a two-electrode configuration employing a Li+ non-aqueous electrolyte environment. Slow scan cyclic voltammetry (SSCV) revealed the redox property of the material between the voltage window 3.5 and 1.5 V Galvanostatic tests exhibited a well discernible discharge-charge profile with a reversible capacity of 170 mA h/g over the potential window of 3.5-1.5 V (C) 2004 Elsevier B.V. All rights reserved.